To Conduct a Study on Gen Z’s Perception of Discounts Available Through Zomato Gold Membership in Ahmedabad - vasani, Meet; Prajapati, Krutika; Vidani, Jignesh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates Gen Z's perceptions of discounts available through the Zomato Gold membership program in Ahmedabad. Utilizing a quantitative approach, data were collected from 149 respondents, focusing on their awareness, beliefs, and behaviors related to the program. The findings reveal a significant association between age and education level, indicating that educational background influences consumer perceptions of value. However, no significant correlation was found between age and employment status, suggesting diverse employment experiences within this demographic. While discounts were acknowledged as a factor in dining decisions, they were not the primary motivator, indicating that factors such as brand loyalty and service convenience play a critical role in their engagement with Zomato Gold